Seed moisture content as a primary trait regulating the lethal temperature thresholds of seeds. (11th December 2018) - Tangney, Ryan; Merritt, David J.; Fontaine, Joseph B.; Miller, Ben P.
Abstract: Fire has long shaped biological responses of plants and plant communities in many ecosystems; yet, uncontrolled wildfire frequently puts people and infrastructure at risk. Fuel or hazard reduction burning outside of the historic fire season is a common and widespread practice aimed at reducing the risk of high‐severity fires, which ideally also considers biodiversity values. Within fire‐prone systems, seed banks are critical for plant species' regeneration, and seeds are typically adapted to survive the passage of fire and to regenerate in response to cues associated with historic fire regimes. However, species‐specific tolerances to the heat from fire exist; likely influenced by a range of physical, physiological, and morphological seed traits, which may differ between seasons. The identification of these tolerances and associated seed traits may inform fire and species management. We determined the lethal temperatures for seeds in relation to their moisture content, and other key traits that we hypothesised may be associated with survival. Seeds from 14 native species and 4 species non‐native to fire‐prone Mediterranean climate Banksia woodlands of south‐west Western Australia were exposed to temperatures between 50 and 180°C for 3 min at three different moisture contents. The temperature at which half the seeds were killed ( T 50 ) was estimated using nonlinear modelling. Seed mass, seed shape, embryo type, plant resprouting ability, seed storage syndrome, and native/non‐native status were quantified and modelled for their relationship with T 50 . Increased moisture content was a significant predictor of elevated seed mortality. Seeds with higher moisture (95% relative humidity [RH]) content perished at much lower temperatures. Seeds with low moisture content (15% or 50% RH) were able to survive significantly higher temperatures (median increase of 38 and 31°C higher respectively). Seeds with basal embryos showed significantly lower T 50 than other embryo types. Synthesis . Seeds with elevated moisture contents have lower lethal temperature thresholds, leading to increased seed mortality during fire events when seeds (and soils) are moist. Thermal tolerance varied among coexisting species within this fire‐prone system. These data suggest potential concern for the impacts of aseasonal burning practices (i.e., cool/wet season burning), and highlight the importance of taking seed moisture content into account when planning and implementing prescribed burning. Abstract : Seeds with elevated moisture contents have lower lethal temperature thresholds, potentially leading to increased seed mortality during fire events when seeds are wet. Thermal tolerance varied among coexisting species within this fire‐prone ecosystem. These data suggest potential concern for the impacts of aseasonal burning practices (i.e. cool/wet season burning), and highlight the importance of taking seed moisture content into consideration when planning and implementing prescribed burning.